Seroprevalence against Rickettsia and Borrelia Species in Patients with Uveitis: A Prospective Survey. (26th November 2017) - Madsen, Kim B.; Wallménius, Katarina; Fridman, Åke; Påhlson, Carl; Nilsson, Kenneth
Abstract : Vector-borne diseases such as Lyme borreliosis and rickettsioses have been associated with ocular inflammation. Our aim was to study patients with diagnosed uveitis to evaluate serological signs of infection or exposure to these tick-borne agents. Forty-eight patients were prospectively examined with serology together with medical records and a questionnaire concerning previous exposure, diseases, and treatments. Seven patients (14.6%) showed seroconversion to Rickettsia spp. between acute and convalescent phase sera, which provides support for a positive Rickettsia diagnosis according to guidelines. The specificity was confirmed by Western blot. Additional 28 patients had stationary titres of which eight (16.6%) had 1 : 256 or higher titre in the first serum, and another 13 patients were seronegative. No epidemiological risk factor or marker could be identified. For Borrelia, only three patients showed moderate IgG titres. A control group of 100 blood donors, 60 patients with rheumatic disease, and 56 patients seeking medical care were tested of which 2.0–7.1% showed low anti- Rickettsia titres and 3.0–8.3% anti- Borrelia titres. The findings are indicative for an association between infection or exposure to Rickettsia spp. and uveitis with a seropositivity among patients with recurrent uveitis in concordance with the spread of rickettsial exposure in a tick-exposed population.